2021
DOI: 10.32332/an-nabighoh.v23i1.2317
|View full text |Cite
|
Sign up to set email alerts
|

Implementasi Metode Mimicry Memorization (Mim-Mem) Dalam Pembelajaran Mufrodat

Abstract: This study aimed to analyze Arabic vocabulary mastery level of students and the process of implementing learning with the Mimicry Memorization method. This research method was quantitative research with an experimental approach. The study was conducted at Muhammadiyah Junior High School Pekalongan. Samples of this research were 25 students of class VII. Data collection methods were observation and tests. The observation method was used to get data on the process of implementing Arabic learning. The test method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…By these two-way direct communication activities, the students are required to imitate and remember or memorize or re-collect what they memorize . This method is called Tharîqatu al-Simᾱ' wa Al-Muhᾱfadzah in which the students memorize the vocabulary after listening to them (Fatati & Sutarjo, 2021). Mimicry-Memorization is derived from the word "memory" which means remember.…”
Section: The Mimicry-memorization Methods In Language Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…By these two-way direct communication activities, the students are required to imitate and remember or memorize or re-collect what they memorize . This method is called Tharîqatu al-Simᾱ' wa Al-Muhᾱfadzah in which the students memorize the vocabulary after listening to them (Fatati & Sutarjo, 2021). Mimicry-Memorization is derived from the word "memory" which means remember.…”
Section: The Mimicry-memorization Methods In Language Learningmentioning
confidence: 99%
“…The other related-study on this topic is conducted by Fatati and Sutarjo with focuses on the implementation of this method in vocabulary learning. The result revealed that this method can develop students' competency in learning vocabulary, in addition, it is a fun way and attract students to be more active because they participate in the teaching and learning process (Fatati & Sutarjo, 2021). This study, moreover, employed several basic MIMIMO procedures to teach vocabulary in the most enjoyable and attractive way for students.…”
Section: Introductionmentioning
confidence: 96%
“…Salah satunya dengan menggunakan berbagai metode, strategi, dan model pembelajaran yang relevan dengan mata pelajaran dan karakteristik siswa. 10 Metode yang baik tidak hanya berdiri sendiri tetapi didampingi dengan media pembelajaran yang memudahkan proses belajar mengajar. Setiap metode pembelajaran bisa menggunakan banyak media sebagai alternatif menyempurnakan metode pembelajaran.…”
Section: Pendahuluanunclassified
“…Several previous studies have explored the application of the Mimicry-Memorization (Mim-Mem) Method in Arabic language learning, focusing on students' mastery of vocabulary and mufradat. Afrida Fatati and J. Sutarjo (2021) Through this research, it is expected to find effective solutions to enhance students' Arabic speaking skills, making the learning process more optimal and supportive of achieving Arabic language learning goals in schools.…”
Section: Introductionmentioning
confidence: 99%